Изучение генеративной фазы развития видов рода Picea Dietr., интродуцированных в Донецком ботаническом саду НАН Украины - Суслова, Е.П. (Промышленная ботаника, 2002)
The results of the ten-year study of the generative development of the 15 genus Picea Dietr. species under introduction in the Ukrainian south-east are presented. Analysis of the plants entering into the reproductive phase has been performed depending on the age of culmination of the current height increment. Level of generative development of the species has been determined. It have been indicated that eight of the introduced species produced full value seeds. The conclusion is being made as for the species of the fourth stage of generative development being tolerant under the conditions of the Ukraine’s south-east and can be employed in landscape gardening.